Ultrafast long-range charge separation in organic semiconductor photovoltaic diodes - Gélinas, Simon; Rao, Akshay; Kumar, Abhishek; Smith, Samuel L; Chin, Alex W; Clark, Jenny; van der Poll, Tom S; Bazan, Guillermo C; Friend, Richard H (Science (American Association for the Advancement of Science), 2014)
Understanding the charge-separation mechanism in organic photovoltaic cells (OPVs) could facilitate optimization of their overall efficiency. Here we report the time dependence of the separation of photogenerated electron hole pairs across the donor-acceptor heterojunction in OPV model systems. By tracking the modulation of the optical absorption due to the electric field generated between the charges, we measure ~200 millielectron volts of electrostatic energy arising from electron-hole separation within 40 femtoseconds of excitation, corresponding to a charge separation distance of at least 4 nanometers. At this separation, the residual Coulomb attraction between charges is at or below thermal energies, so that electron and hole separate freely. This early time behavior is consistent with charge separation through access to delocalized π-electron states in ordered regions of the fullerene acceptor material.